Нечіткий метод індуктивного моделювання в задачах прогнозування макроекономічних показників - Zaychenko, Yu. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A fuzzy group method of data handling is considered. The basic ideas and principles of this method are presented. The problem of adaptation of the fuzzy models after obtaining of new experimental data is investigated. The influence of different membership functions of fuzzy coefficients on the forecast precision is analysed. The results of method applications of the fuzzy for macroeconomic indexes forecast are presented and discussed.